Graphene-based beam-reconfigurable liquid antenna for 5G mmWave wireless systems - Dash, Sasmita; Psomas, Constantinos; Krikidis, Ioannis (Frontiers in Communications and Networks, 2025)
The advancement of wireless technologies has led to significant progress in antenna design in order to meet the continuously increasing demands. Liquid antennas have gained significant interest in research owing to their distinctive properties, such as being small, flexible, transparent, and capable of reconfiguration. Recently, graphene liquid has been considered for various applications because of its affordability, excellent conductivity, flexibility, transparency, and easy processing. This paper presents a beam-reconfigurable graphene liquid antenna. The movement of the graphene liquid within the microfluidic channel enables beam reconfiguration. The antenna is realized in a rectangular microfluidic channel made of polymethyl methacrylate over a liquid crystal polymer substrate. The proposed antenna performs beam-steering up to 360° with 7 dBi of gain and operates at 28 GHz with a wideband of 10-dB impedance bandwidth of over 20%. In particular, the main beam of the antenna reconfigures into six directions (0°,45°,135°,180°,225° and 315°)at the operating frequency. Moreover, the antenna offers a consistent reflection coefficient at 28 GHz in each of the six reconfigurable frequencies. Therefore, the proposed novel technique for designing reconfigurable antennas using graphene liquid holds great promise for 5G mmWave wireless communication systems.